The Effect of Video Feedback on Adult ESL Learners' Paragraph Writing Skills - B.N. Thennakoon; L. Abesooriya (The Open University of Sri Lanka, 2022)
Writing and the provision of feedback in English as a Second Language classrooms are crucial factors. Feedback provision is one of the productive approaches to improving learners' writing performance in the ESL context. With the continuous evolution of technology, the methods of feedback have also varied and advanced. Even though teacher-written feedback is the most frequently used type of feedback, studies have discovered the use of teacher-written feedback is indecisive since the learners face difficulties in comprehending the teacher's feedback. Therefore, there is a continuing dispute over the efficacy of teacher-written feedback. The present study addresses the dearth of research in the provision of video feedback for ESL writings in Sri Lanka and aims to contribute to the areas in which further research is needed. For this, an experimental quantitative research design was used. The empirical data for the study was gathered through the comparison of 20 participants' multiple drafts of writing paragraphs over a five-week period and error analysis sheets were employed to track the errors in their writings. The results reveal that the participants in the experimental group incorporated higher levels of correction from two respective video feedback into their proceeding drafts than the participants in the control group who received two particular written feedback for two written texts during the study. The findings obtained from this study convey that video feedback is a pertinent practice in ESL writing. Hence, the requirement for more research to recognize cause and effect relationships of video feedback for writing is highlighted in the present study.